UTILISATION OF BRINE-DETOXIFIED THEVETIA (Thevetia neriifolia Juss) SEED FOR BROILER FEED PRODUCTION (2012)
Conventional dietary plant protein sources for broilers are expensive thereby increasing cost of production. Cheaper but equally nutritive sources of plant protein are currently being explored. Thevetia Seed (TS), though rich in protein has limited use due to intrinsic antinutritional factors, which if detoxified could be harnessed. Information on detoxification and the use of TS in broiler production is scanty. Detoxification of TS and its utilisation in broiler feed production were therefore investigated. One hundred grams of TS was soaked in water, ethanol (24 hours) or in 2.5, 5.0 and 7.5% brine solution for 2, 3 or 4 hours. The samples were either sun-dried for 3 days or toasted after soaking and thereafter analysed for chemical and residual glycoside composition. Treatment with the lowest residual glycoside was incorporated as TS Meal (TSM) to be a substitute for soyabean meal in broiler starter and finisher diets at 0, 25, 50, 75 and 100%. Two hundred 1- day old broilers were randomly allotted to five dietary treatments with four replicates of ten birds each. They were fed starter diets from day1-28 and finisher from day 29- 56. At weeks 4 and 7, blood samples from two birds per replicate were collected for serum biochemical and haematological analyses. In the last seven days of the experiment, 0.5% titanium dioxide indigestible marker was added to the diets to determine Apparent Ileal Digestibility (AID). Two birds per replicate were slaughtered for digesta collection and carcass characteristics. Other indices measured were Feed Intake (FI) and Weight Gain (WG). Data were analysed using descriptive statistics and ANOVA at p= 0.05. Toasting significantly reduced crude protein in water and ethanol treated samples from19.35 in raw sample to 18.14 and 18.43%, respectively. Crude protein increased significantly in sun-dried water (22.1%) and brine treated (23.1%) samples. The TS soaked in 7.5% brine for 3 hours significantly increased crude protein from 23.1% to 44.87% and reduced glycoside content from 4.7% to 0.07% (98.51% reduction of glycoside). Variations in haematological and serum biochemical indices were not significantly different in values for birds on all treatments except in the levels of albumin, calcium, glucose and potassium ions at the finisher phase. The FI (105.8 ±0.7 g/bird) and WG (25.7 ±0.4 g/bird) at the starter phase were significantly reduced to 92.5 ± 0.9 g/bird and 21.2 ±0.4 g/bird for birds on 100% TSM (p < 0.05). Similar trend was observed for FI at the finisher phase which reduced from 176.4±5.7 to 118.6 ±1.1 g/bird. Birds on 50% TSM recorded highest values for live weight 1824.7 ±0.9 g/bird, dressed weight 1220.2 ±0.3 g/bird, breast 304.1 ±0.9 g, thigh 216.8 ± 0.6 g and AID coefficient of crude protein (0.79). Detoxification with 7.5% brine for three hours best improved the nutritive value of Thevetia seed. Thevetia seed meal was well utilised and an enhanced apparent Ileal digestibility was achieved. Thevetia seed meal replaced up to 50% soyabean meal